2014
DOI: 10.1186/1756-3305-7-121
|View full text |Cite
|
Sign up to set email alerts
|

Rickettsiaceae and Anaplasmataceae infections in Ixodes ricinus ticks from urban and natural forested areas of Poland

Abstract: BackgroundIxodes ricinus is a major vector for a range of microbial pathogens and the most prevalent and widely distributed tick species on the European continent, occurring in both natural and urban habitats. Nevertheless, little is known about the relative density of ticks in these two ecologically distinct habitats and the diversity of tick-borne pathogens that they carry.MethodsWe compared densities of questing I. ricinus nymphs and adults in urban and natural habitats in Central and Northeastern Poland, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
63
2
3

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 77 publications
(78 citation statements)
references
References 54 publications
10
63
2
3
Order By: Relevance
“…High levels of genetic diversity in Rickettsiales have been identified in both ticks and vertebrates61436, including multiple infection by distinct bacteria in a single tick species1837. Our phylogenetic analysis revealed the co-circulation of nine documented and five tentative species bacteria, as well as three symbionts/endosybionts in five species of mosquitoes.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…High levels of genetic diversity in Rickettsiales have been identified in both ticks and vertebrates61436, including multiple infection by distinct bacteria in a single tick species1837. Our phylogenetic analysis revealed the co-circulation of nine documented and five tentative species bacteria, as well as three symbionts/endosybionts in five species of mosquitoes.…”
Section: Discussionmentioning
confidence: 78%
“…Strikingly, although the mosquito Anaplasma bacteria (ZJARSA-8, WHANSL-27–1, JXARSA-29, WHAEAL-17-2, JXANSA-19, WHARSL-30, WHAEAP-26) were most closely related to A. platys bacteria in both the rrs and groEL trees, in the gltA tree they grouped with strain Anaplasma sp. clone SY124 previously identified in ticks from Shenyang of China36. Further studies are needed to determine whether these bacteria belong to A. platys or represent co-infection (and/or recombinant event).…”
Section: Resultsmentioning
confidence: 99%
“…The DNA sequences amplified from our human "Ca. Neoehrlichia mikurensis" isolates were also identical to those obtained from ticks and bank voles collected in Warmiń sko-Mazurskie province in our previous studies (5). However, the phylogenetic tree of the partial groESL operon sequences showed that two European "Ca.…”
mentioning
confidence: 76%
“…It has been detected in Mongolia [12], China [6,12,13], Japan [1,14], Russia [4,5,15,16], the Czech Republic [9,17,18], Slovakia [19][20][21], Moldova [22], Hungary [23][24][25], Austria [18,26], Germany [11,[27][28][29][30][31][32], Switzerland [33][34][35][36][37], Poland [38,39], Romania [40], France [28,41,42], Belgium [43], Italy [44][45][46], Spain [47], The Netherlands [3,42,43,48], and the Scandinavian countries [2,…”
Section: The Agentmentioning
confidence: 99%